GROUNDWATER CONTAMINATION BY NUTRIENTS: CASE OF GADAÏNE-AIN YAGHOUT PLAIN (NORTH OF BATNA), ALGERIA. (Sciences & Technologie. D, Sciences de la terre, 2017)
In Algeria, groundwater face a risk of degradation due to uncontrolled releases, intensive and indiscriminate use of chemical fertilizers in agriculture as well as disorderly exploitation of this resource. The consequences are a chemical modification of the water, making it unsuitable for desired uses, which makes the field of water increasingly vital and fragile requiring for its preservation monitoring and control of the management of this resource. To determine the causes of the progressive degradation of the chemical quality of groundwater, this study was devoted to the knowledge of the geological and hydrogeological characteristics of the plain Gadaïne - Ain Yaghout (North of the city of Batna) and interpretation of physico-chemical analysis of water samples with highlighting the various sources of pollution and their impact on groundwater of the plain.